A new beginning : the establishment of the biodynamic movement in New Zealand 1930-50 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University, Manawatu, New Zealand - Dib, Guilherme Barreto (Massey University, 2018)
One of today’s greatest societal concerns is environmental and health issues. The understanding that these issues are strongly linked to conventional agriculture and its widespread use of pesticides, herbicides and fertilizers is becoming more widely accepted. To this end Biodynamic farming and gardening has presented itself as an alternative way to produce food, arguably of the highest quality, while maintaining a sound natural and sustainable method of working the land. Growers in New Zealand began to apply this form of farming developed in Germany in 1924 and taken up in New Zealand by 1929/30. By 1939 they organized themselves in order to promote Biodynamic principles and methods by forming the ‘Rudolf Steiner Bio Dynamic Association in New Zealand’ in 1939, later renamed the ‘Biodynamic Farming and Gardening Association in New Zealand’. For a period of time the Association was “the best organized and the fastest growing organic group in the country”.1 Within their Association, meetings and gatherings were held as well as field days and farm visits. They also produced numerous publications. Since then, an increasing though still relatively small number of people, approximately 25 in 1940 to over 300 members in 1950, has committed themselves to this unique way of growing food. Biodynamic farming advocates influenced a group of farmers, gardeners and food growers in this country and properties were converted into a Biodynamic regime. Biodynamic farming and gardening has offered an alternative reference point to the mainstream pastoral agriculture in New Zealand which was orthodox and based on use of fertilizers, scientifically driven, increasingly industrialized and predominantly export oriented as the 20th century unfolded.
Keywords: Rudolph Steiner Biological-Dynamic Association in New Zealand for Soil and Crop Improvement; History; Biodynamic Farming and Gardening Association (in New Zealand); Biodynamic agriculture; Organic gardening; Anthroposophy